Laparoscopic gastrectomy for remnant gastric cancer: Risk factors associated with conversion and a systematic analysis of literature. (October 2016) - Liao, Guanqun; Wen, Shunqian; Xie, Xueyi; Wu, Qing
Abstract: Background: In traditional opinion, history of abdominal surgery was the relative contraindication for Laparoscopic gastrectomy (LG) with high rate of conversion to Open gastrectomy (OG).Use of LG for treatment of remnant gastric cancer (RGC) has been documented in some case studies and controlled clinical trials. However, whether LG is superior, equal or inferior to OG in these patients is not clear. Methods: English language articles published between January 2005 and January 2016 were searched in MEDLINE, Embase and the Cochrane Database of Systematic Reviews. Main outcome measures were: conversion of LG to OG, operative time, intraoperative blood loss, tumor size, positive proximal resection margin, lymph node dissection, disease stage, post-operative resumption of oral intake, postoperative hospital stay, complications, mortality and follow-up findings. Published clinical data which was in the situation of conversion to OG was collected, and the factors associated with conversion to open surgery were examined. Results: Five non-randomized controlled trials and seven LG case studies were included in the systematic review. Meta-analysis of the data could not be performed due to high variation and heterogeneity in study design, study population, LG technique, and outcome measures among the included studies. Systematic analysis of the included studies showed that LG was associated with significantly shorter mean operative time, early resumption of oral intake, and shorter hospital stay, as compared to that with OG. No significant difference in complications was observed between the two groups. Conclusion: LG in the hands of experienced surgeons is relative feasibility and safety for RGC. Previous surgical anastomosis, previous open surgery and surgical experience were associated with conversion to OG. However, these findings should be validated with robust prospective comparative studies. Highlights: LG is a feasible, effective and safe procedure for curative treatment of RGC. LG is hypothesized to be superior to OG for curative treatment of RGC. It is the first report to summarize the feasibility, efficacy and safety of LG.